ECMO During Combined Heart-Kidney Transplantation: A Case Report. Issue 2 (February 2020) - Chazin, Shai M.; Bresticker, Michael A.; Chhabra, Darshika; Mital, Deepak; Desai, Chaitanya R.; Slakey, Douglas P.
Abstract : Combined heart-kidney transplantation (CHKT) is a therapy for a carefully selected subgroup of patients with concomitant heart and kidney failure. Discerning whether there is reversible or irreversible kidney disease is crucial to selection for CHKT versus heart transplant alone to optimize therapeutic value and organ allocation. Methods for determining extent of kidney disease include estimating glomerular filtration rate, creatinine clearance, kidney ultrasonography, and kidney biopsy. Additionally, the use of extracorporeal membrane oxygenation (ECMO) in the setting of CHKT only recently emerged as feasible. We present a case of a 69-year-old man with cardiogenic shock who was placed on venoarterial-ECMO (VA-ECMO) following orthotopic heart transplant (OHT) due to severe mediastinal bleeding and remained on VA-ECMO during kidney transplant. To our knowledge, this is the second report of a patient undergoing kidney transplant while on VA-ECMO following OHT.